Analisa Perbandingan Economic Value Added (Eva) Dan Return On Asset (Roa) Dalam Menilai Kinerja Perusahaan - Dewi Silvia (Universitas Bandar Lampung (UBL), 2020)
The purpose of this researchtoassess the performance of companies in cigarette companies listed on the Indonesia Stock Exchange (IDX) for 4 years (2015-2018) by using EVA and ROA analysis. This type of research is quantitative research. The population in this study is the cigarette companies listed on the IDX. The sampling technique uses purposive sampling so that PT. Gudang Garam Tbk andPT. Bentoel Internasional Investama as samples. The analytical tool used is to use the comparison of EVA and ROA. Based on the calculation results of PT. Gudang Garam Tbk in 2015-2018using ROA shows that the ROA value exceeds 1 and the EVA value shows a result less than zero or negative. While the value of ROA at PT. Bentoel Internasional Investama shows results exceeding 1 and the EVA value is less than zero or negative. Where If seen from the results of calculations using the application of the concept of EVA at PT. Gudang Garam Tbk and PT. Bentoel Internasional Investama Tbk. These results indicate that the management has not been able to produce the profits expected by shareholders. Which means that the rate of return generated by the company does not match what is expected by the investor and the costs cannot be met.